Microwave-assisted synthesis of sec/tert-butyl 2-arylbenzimidazoles and their unexpected antiproliferative activity towards ER negative breast cancer cells - Abdul Rahim, Aisyah Saad; Muhamad Salhimi, Salizawati; Natarajan, Arumugam; Lim, Chung Pin; Ng, Shy Yee; Muttiah, Nithya Niranjini; Wong , Boon Keat; Abd Hamid, Shafida; Osman, Hasnah; Mat, Ishak (Informa UK, Ltd., 2013)
A new series of N-sec/tert-butyl 2-arylbenzimidazole derivatives was synthesised in 85–96% yields within 2–3.5 min by condensing ethyl 3-amino-4-butylamino benzoate with various substituted metabisulfite adducts of benzaldehyde under focused microwave irradiation. The benzimidazole analogues were characterised using 1H NMR, 13C NMR, high resolution MS and melting points. Evaluation of antiproliferative activity of the benzimidazole analogues against MCF-7 and MDA-MB-231 revealed several compounds with unexpected selective inhibitions of MDA-MB-231 in micromolar range. All analogues were found inactive towards MCF-7. The most potent inhibition against MDA-MB-231 human breast cancer cell line came from the unsubstituted 2-phenylbenzimidazole 10a.